The effectiveness of ICT in teaching physics - Turekhanova, K.M.; Akimkhanova, Zh.Ye.; Gani, J. (Recent Contributions to Physics, 2019)
In the 21st century, the modern employment cannot be imagined without the using of information and communication technology (ICT). Information technology is a set of mathematical and cybernetic techniques that provide the collection, storage, processing and transportation of information on the basis of modern computer technology. Among all educational disciplines, physics is able to easily maintain a computer subject. For a long time the computer has been successfully used here to facilitate the routine work of performing calculations. But information communication technologies can also be used to study theoretical material, training, as a means of modeling and visualization, etc. The choice depends on the goals, objectives and stage of the lesson (explanation, consolidation, repetition of the material, knowledge test, etc.). The most effective way of world informative education space is to fully supply ICT to each branch of education. This paper shows that the use of modern innovative educational methods and technologies is an important component for organizing an effective educational process in physics lessons. The process of informatization in education raises the level of training of teachers, students and the quality of the profession. It allows the student to self-development, self-education and creativity.